2009
DOI: 10.1177/0261927x09335253
|View full text |Cite
|
Sign up to set email alerts
|

“Should Be Fun—Not!”

Abstract: according to Kreuz's principle of inferability, speakers tend to employ nonliteral language when it can reasonably be perceived by their conversational partner. In a computermediated communicative setting, such as e-mail, this suggests that the e-mail writer might use discourse tools that facilitate comprehension on the part of the recipient. The present study examined rates of usage for various forms of nonliteral language in 210 e-mail messages written by young adults. In 94.30% of all e-mails there was at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…It covers a wide range of expressions, such as idioms, metaphors, irony and jokes, hyperbole, indirect requests, as well as other stereotyped expressions, such as cliches. A recent study investigating the incidence of non-literal expressions in e-mails written by young people found that 94.30% of the e-mails included at least one non-literal statement, and participants used on average 2.90 non-literal expressions per e-mail (Whalen, Pexman, & Gill, 2009). Figurative language is commonly characterized as non-transparent in various ways: the comprehender has to go beyond the literal meanings of the constituent words in a figurative expression in order to recover the speaker's intended meaning.…”
Section: Figurative Language Processingmentioning
confidence: 99%
“…It covers a wide range of expressions, such as idioms, metaphors, irony and jokes, hyperbole, indirect requests, as well as other stereotyped expressions, such as cliches. A recent study investigating the incidence of non-literal expressions in e-mails written by young people found that 94.30% of the e-mails included at least one non-literal statement, and participants used on average 2.90 non-literal expressions per e-mail (Whalen, Pexman, & Gill, 2009). Figurative language is commonly characterized as non-transparent in various ways: the comprehender has to go beyond the literal meanings of the constituent words in a figurative expression in order to recover the speaker's intended meaning.…”
Section: Figurative Language Processingmentioning
confidence: 99%
“…Previous literature on the topic mainly focused on the impact of speaker accent on the comprehension of literal meaning. The present study explores, for the first time, the impact of a foreign accent on figurative language interpretation; a phenomenon that is pervasive in daily conversations [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…However, most daily conversational exchanges contain some form of figurative language [1,2], where the ultimate meaning of the discourse does not correspond to the simple sum of the lexical items. To our best knowledge, there is no study on the role of speaker identity on figurative language interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Irony is a common form of figurative language, widespread across cultures and languages (Booth 1974). Its use has been documented in conversations between adult friends (Gibbs 2000;Tannen 2005), in family interactions Recchia et al 2010), in the classroom (Ely and McCabe 1994), and even in communicative contexts devoid of gesture, facial expression or tone of voice information, as in blogs ) and email (Whalen et al 2009). Irony comprehension is an important aspect of pragmatic language skills, and one that is challenging for typically developing children (e.g., Capelli et al 1990;Filippova and Astington 2008;Winner 1988), for many clinical populations (e.g., Dennis et al 2013;Happé 1993;Langdon et al 2002) and for second-language learners (e.g., Bouton 1999;Kim 2014).…”
Section: Introductionmentioning
confidence: 99%